PHYTOCHEMICAL SCREENING AND ANTIOXIDANT ACTIVITY TEST OF ARA FRUIT EXTRACT (Ficus racemosa Linn.) USING DPPH METHOD - Hidayanti, Baiq Rauhil; Novia Suryani; Yuli Kusuma Dewi (SPIN JURNAL KIMIA & PENDIDIKAN KIMIA, 2023)
Ficus racemosa Linn. is a native Indonesian plant known as the ara plant in Lombok or Elo in East Java. The fruit has a fragrant aroma, soft texture, mild sweet taste and a little sour. Presence of ara (Ficus racemosa Linn.) is mostly known as one of the plants whose fruit can only be eaten and used as a medicine for diarrhea, but the compounds contained in ara are not yet known, so research is needed. The purpose of this study was to determine the secondary metabolit content of ara fruit extract and antioxidant activity using the DPPH method. Ara fruit was extracted by maceration method using methanol solvent. The results of the phytochemical screening showed that the ara fruit extract contained secondary metabolites, such as flavonoids, steroids, saponins and tannins. Antioxidant activity (IC50) extract of ara with various concentrations of 25; 50; 75; 100; and 125 ppm soul a value of 65.042 ppm. Based on the results of antioxidant activity, it can be seen that ara fruit extract is classified as a strong antioxidant.